INTEGRATION OF FINE ARTS STUDIES AND ISLAMIC EDUCATION IN EARLY CHILDHOOD EDUCATION: DEVELOPMENT OF CHILDREN’S RELIGIOUS, MORAL, AND AESTHETIC VALUES - Anugrah, Yuwan Fijar; Setiawan, Yukki; Kurnia, Galih Jatu; Witjaksono, M Dimas Yudi (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study explores the integration of Islamic visual arts in early childhood education, emphasizing their role in fostering children’s religious, moral, and aesthetic development. The research adopts a qualitative literature study by analyzing relevant journal articles, books, and educational reports. Findings indicate that Islamic visual arts, such as mosque drawing, simple calligraphy tracing, and geometric painting, function as effective media for strengthening children’s fine motor, cognitive, and aesthetic skills, while simultaneously instilling Islamic values and moral principles. Teachers act as facilitators and role models, bridging the connection between artistic experiences and religious values. The study concludes that Islamic art-based learning provides transformative opportunities in early childhood education by uniting creativity and spirituality. This research contributes theoretically to the development of art-based Islamic pedagogy and offers practical implications for teachers in designing creative, value-laden curricula. Future studies are recommended to apply empirical and experimental approaches to examine the long-term impacts of Islamic art education in various cultural contexts.